Financialization of agricultural commodities and agribusiness economics in Brazil: notes on its implications for the rise of land conflicts (2019)
The articulation between commodities financialization and the global race for lands is an essential object of reflection in the contemporary debate. These movements have been associated with multiple processes ranging from the increased Chinese demand for raw materials to land grabbing in countries with abundant natural resources in Latin America and Africa. With an emphasis on the implications of these processes in Brazil, this article aims at identifying the relations between the systemic economic dynamics and the configuration of an agribusiness economy and its implications for the increase of territorial conflicts and the worsening of the land issue. The methodology consists of a critical review of the literature and analysis of institutional information. The article highlights that the greater complexity of the regime of contemporary accumulation is associated with intense territorial appropriation and the expansion of land conflicts in Brazil.